2020
DOI: 10.1021/acs.est.0c04740
|View full text |Cite
|
Sign up to set email alerts
|

Testing Removal of Carbon Dioxide, Ozone, and Atmospheric Particles by Urban Parks in Italy

Abstract: Cities are responsible for more than 80% of global greenhouse gas emissions. Sequestration of air pollutants is one of the main ecosystem services that urban forests provide to the citizens. The atmospheric concentration of several pollutants such as carbon dioxide (CO2), tropospheric ozone (O3), and particulate matter (PM) can be reduced by urban trees through processes of adsorption and deposition. We predict the quantity of CO2, O3, and PM removed by urban tree species with the multilayer canopy model AIRTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 60 publications
1
11
0
1
Order By: Relevance
“…Parks are important places within the urban context as other studies have already demonstrated that their characteristics are associated with better conditions regarding thermal, visual, acoustic, and air quality domains (Cohen et al 2014 ; Fares et al 2020 ; Pioppi et al 2021 ; Jo and Jeon 2021b ). The two investigated parks showed to be different in terms of physical parameters registered when comparing them through statistical tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parks are important places within the urban context as other studies have already demonstrated that their characteristics are associated with better conditions regarding thermal, visual, acoustic, and air quality domains (Cohen et al 2014 ; Fares et al 2020 ; Pioppi et al 2021 ; Jo and Jeon 2021b ). The two investigated parks showed to be different in terms of physical parameters registered when comparing them through statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…In general, parks are key spots in urban spaces as they provide environmental and social benefits, promoting physical activities practice, reducing stress, and boosting social connections (Jiang et al 2019). Moreover, these places reduce air pollution (Fares et al 2020) and mitigate urban microclimate (Pioppi et al 2021). The cooling effects of urban parks have been extensively studied (Lu et al 2017;Yan et al 2018;Aram et al 2020;Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Le zone urbane e peri-urbane sono sistemi in cui vive il 54% della popolazione mondiale, dove si consuma il 70% dell'energia globale e l'80% del cibo e dove vengono emessi il 75% degli inquinanti e dei gas serra (United Nations Human Settlements Programme -UN-HSP 2011). Le nuove foreste urbane, così come il recupero funzionale e la gestione della vegetazione esistente, possono avere un ruolo fondamentale nella mitigazione degli estremi climatici (attraverso la riduzione della temperatura per ombreggiamento e l'azione rinfrescante dell'evapotraspirazione -Norton et al 2015), nella riduzione dell'inquinamento atmosferico (Fares et al 2020) e nella riduzione dei fenomeni alluvionali. Le periferie sono ad oggi interessate da un problema grave quanto la deforestazione: il consumo di suolo, cioè l'occupazione di una superficie originariamente naturale, seminaturale o agricola con una copertura artificiale permanente e spesso impermeabile.…”
Section: Forest@ Forest@ --Rivista DI Selvicoltura E Rivista Di Selvi...unclassified
“…The Aggregated InteRpreTation of the eneRgy balance and water dynamics for Ecosystem sErvices assessment (AIRTREE) model is a multi-layer model that couples soil, plant and atmospheric processes to simulate exchanges of CO2, H2O, O3, and PM between leaves and the atmosphere. A detailed description of the AIRTREE model can be found in Fares et al (2019Fares et al ( , 2020, so here we confine ourselves to a description of the coupled stomatal conductancephotosynthesis parameterization and ozone deposition scheme.…”
Section: The Airtree Modelmentioning
confidence: 99%